Diversification of Farmer Income in West Java - Wardhana, Adhitya; Handayani, Reni Tri; Pamungkas, Eksa (AFEBI Economic and Finance Review, 2017)
Agricultural land has decreased the impact on farmers in meeting their needs. The transition to agriculture complicates industry in its effort to meet the needs of farmers. Another issue, climate change will disrupt plant crops that will result in inefficient farming. Farming inefficiencies are a reason for farmers to diversify. This study was based on a micro data survey data of agricultural enterprise household income in the Regencies / Cities of West Java on a household level. Limits of household income diversification of farming is when the household has to venture outside the agricultural sector or one of the cores and the sources of income comes from salaries / wages of laborers / employees outside the agricultural sector. The results showed that with the increasing age of the household head the diversity decreases, the higher the education of the head of household the more it encourages the diversification of income, the more the additional land area increases diversification, the easier access to credit for adding revenue diversification, increasing the income of farmers that tend not to diversify, the more houses and stairs in school which support farmers to diversify, the more productive the household income lowers with diversification. JEL Classification: D31, O12, O13Keywords: Climate Change, Diversify, Diversity of Income, Farming, Inefficiency